Applying Schema Theory in Teaching Reading Comprehension - Jufri Jufri (Universitas Negeri Padang, 2014)
This paper is aimed at discussing reading strategies used by teachers in teaching reading. One of strategies discussed here is schema theory. In this theory, teachers implement types of connections in reading. The connections can be divided into three categories, namely: text-to self connections, text-to world connections and text-to text connections. By applying this schema theory, the students are involved actively in reading activities. The more they are involved in reading, the more they can comprehend the reading text. For this reason, the students should do total involvement, that is, physical and psychological involvements. These involvements are very important because the students will try to comprehend three levels of comprehensions, namely, literal level, inferential level and evaluational level. Reading literally is often called reading on the lines or reading stated information. Meanwhile, reading inferentially is reading between the lines or implied meaning. The last one reading critically is reading beyond the lines or making evaluation toward the writer’s message. These levels of comprehension will affect the students’ comprehension about a reading text. By applying three types of connections in reading, it is expected that the students will be able to increase their reading comprehension.